2023
DOI: 10.3389/fcvm.2023.1215710
|View full text |Cite
|
Sign up to set email alerts
|

Physiological reactivity to acute mental stress in essential hypertension—a systematic review

Abstract: ObjectiveExaggerated physiological reactions to acute mental stress (AMS) are associated with hypertension (development) and have been proposed to play an important role in mediating the cardiovascular disease risk with hypertension. A variety of studies compared physiological reactivity to AMS between essential hypertensive (HT) and normotensive (NT) individuals. However, a systematic review of studies across stress-reactive physiological systems including intermediate biological risk factors for cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 194 publications
0
2
0
Order By: Relevance
“…According to the literature, triglycerides are mainly stored in adipocytes, and hydrolyzed to free fatty acids by adipocyte triglyceride lipase (ATGL) [55]. The mentioned reactions are altered among patients with OSA: oxidative stress increases activation of ATGL, resulting in an increased level of free fatty acids in the bloodstream [56]. Moreover, intermittent hypoxia, which is a stress factor for the organism, stimulates the adrenal gland with consequent noradrenaline and cortisol release, which also stimulates lipolysis [57].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, triglycerides are mainly stored in adipocytes, and hydrolyzed to free fatty acids by adipocyte triglyceride lipase (ATGL) [55]. The mentioned reactions are altered among patients with OSA: oxidative stress increases activation of ATGL, resulting in an increased level of free fatty acids in the bloodstream [56]. Moreover, intermittent hypoxia, which is a stress factor for the organism, stimulates the adrenal gland with consequent noradrenaline and cortisol release, which also stimulates lipolysis [57].…”
Section: Discussionmentioning
confidence: 99%
“…The European Agreement on Work-Related Stress defines stress as a state characterized by physical, psychological, or social complaints or dysfunctions resulting from individuals feeling unable to meet the demands or expectations placed upon them (Broughton, 2004). This definition underscores the global recognition of health-related problems associated with stress (Fisch et al, 2020a;Gnall et al, 2023;Mazure et al, 2023;Popescu et al, 2023;Sara et al, 2023;Walther and Wirtz, 2023). In Germany, a survey of 1,200 adults found that 61% reported experiencing stress either frequently or occasionally (Wohlers and Hombrecher, 2016).…”
Section: Introductionmentioning
confidence: 98%